Decreased Human Leukocyte Antigen-G Expression by miR-133a Contributes to Impairment of Proinvasion and Proangiogenesis Functions of Decidual NK Cells - Guo, Wenwei; Fang, Liang; Li, Bo; Xiao, Xifeng; Chen, Shuqiang; Wang, Jun; Yang, Fang; Chen, Lihua; Wang, Xiaohong (Frontiers in Immunology, 2017)
Human leukocyte antigen (HLA)-G plays a crucial role in conferring fetal-maternal tolerance and ensuring a successful pregnancy. CD56bright nature killer (NK) cells accumulate at the maternal decidua in large numbers during pregnancy and are found in direct contact with fetal trophoblasts. There is increasing evidence that decidual NK (dNK) cells are crucial for pregnancy. However, the regulation of dNK cells is mostly unknown. Here, we provide evidence that the secretion function of dNK cells in recurrent spontaneous abortion (RSA) was impaired, which led to the impairment of the pro-invasion and pro-angiogenesis functions of dNK cells. Decreased HLA-G expression induced by the transfection of miR-133a mimics in HTR-8/SVneo affected the secretory functions of dNK cells. Thus, our data revealed that the functions of dNK cells could be suppressed by the decreased expression of HLA-G and suggest a possible mechanism of recurrent miscarriage.